Long Non-coding RNAs LINC01679 as a Competitive Endogenous RNAs Inhibits the Development and Progression of Prostate Cancer via Regulating the miR-3150a-3p/SLC17A9 Axis - Mi, Yuan-yuan; Sun, Chuan-yu; Zhang, Li-feng; Wang, Jun; Shao, Hong-bao; Qin, Feng; Xia, Guo-wei; Zhu, Li-jie (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNAs (lncRNAs) have been indicated as the candidate factors to predict cancer prognosis. But it is still unknown about whether lncRNA combinations may be utilized for predicting overall survival (OS) of prostate cancer (PCa). This present work focused on selecting the potent OS-related lncRNA signature for PCa and studying its molecular mechanism to enhance the prognosis prediction accuracy. Differentially expressed lncRNAs (DElncRNAs) or differentially expressed genes (DEGs) were obtained based on TCGA database by R software “edgeR” package. lncRNAs or mRNAs significantly related to PCa were screened through univariate as well as multivariate Cox regression, for the construction of the risk model for prognosis prediction. Moreover, this constructed risk model was validated through ROC analysis, univariate regression, and Kaplan-Meier (KM) analysis. Additionally, we built lncRNA-miRNA-mRNA ceRNA network through bioinformatics analysis. Colony formation, CCK-8, flow cytometry, scratch as well as Transwell assays were performed based on PCa cells subjected to small interfering RNA (siRNA) targeting LINC01679/SLC17A9 and vector expressing LINC01679/SLC17A9 transfection. Thereafter, the ceRNA mechanism was clarified via qRT-PCR, Western blotting (WB), RNA pull-down and luciferase reporter assays. Nude mouse tumor xenograft was established to examine LINC01679’s oncogenicity within PCa cells. According to our results, LINC01679 depletion promoted cell proliferation, metastasis, tumor growth, and inhibited cell apoptosis in vivo and in vitro, which was also associated with poor survival. LINC01679 regulated miR-3150a-3p level by sponging it. Importantly, miR-3150a-3p overexpression was related to the increased proliferation and decreased apoptosis of PCa cells. Rescue assays suggested that miR-3150a-3p mimics rescued the repression on PCa progression mediated by LINC01679 up-regulation, but SLC17A9 down-regulation reversed the miR-3150a-3p inhibitor-mediated repression on PC progression. Importantly, SLC17A9 down-regulation rescued the repression on PCa progression mediated by LINC01679 up-regulation. LINC01679 and SLC17A9 are tightly associated with certain clinicopathological characteristics of PCa and its prognostic outcome. In addition, LINC01679 is the ceRNA that suppresses PCa development through modulating the miR-3150a-3p/SLC17A9 axis.